Penerapan Algoritma Linier Congruent Method Pada Pengacakan Soal Ujian Berbasis Online di SD Muhammadiyah Sei Cabang - Debby Ade Prastiwi; Akim M.H. Pardede; Zira Fatmaira (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2024)
This study was conducted at SD Muhammadiyah Sei Cabang, a private school in Langkat Regency, which still uses manual examination methods with identical questions for all students. This method is considered ineffective because it allows students to cheat, leading to exam results that do not accurately reflect their abilities. To address this issue, the study developed a web-based examination system using the Linear Congruent Method (LCM) to generate randomized question numbers. With LCM, each student receives a different set of question numbers, making the exam process more effective and fair. The system was built using PHP programming language and MySQL database, enabling efficient data storage and processing. The implementation of this system resulted in improved accuracy in assessment and reduced cheating potential during exams at the school.